Effects of salubrinal on ER stress in an experimental model of polycystic ovary syndrome. (20th November 2020) - Emincik, Asli; Gungor, Zeynep Banu; Guzel, Elif
ABSTRACT: This study aimed to investigate the role of endoplasmic reticulum (ER) stress in polycystic ovary syndrome (PCOS) and the effect of salubrinal (SAL) on this role. Animals were divided into four groups as control, PCOS, PCOS+SAL and SAL. Weights and serum testosterone levels were increased in the PCOS group while serum LH and ATF4 expressions were decreased. Morphometrically, number of follicles with a diameter between 150 and 300 µm were declined and number of follicles larger than 300 µm as well as the percentage of cystic follicles (CFs) were increased. Immunoreactivities of GRP78 and p-eIF2α were decreased, whereas oxidative stress (OS) dependent PAR expression was increased. Ultrastructurally, the PCOS group had no ER enlargement which was observed in the control group, while there were mitochondrial damage in granulosa cells (GCs). Elevated OS levels did not induce but rather decreased ER stress in GCs, and SAL injection in the PCOS model was ineffective on searched parameters. Since ER stress plays roles in certain physiological processes, we suggest that inhibitors of ER stress may not be always useful for reproductive tissues.